Reforming inheritance tax - Arun Advani; David Sturrock (Institute for Fiscal Studies (IFS), 2023)
We set out issues with the inheritance tax system and examine options for reform and the distributional impacts of reforming or abolishing the tax.
Keywords: 330; Poverty; inequality and social mobility; Savings; pensions and wealth; Taxes and benefits; IFS Green Budget 2023; Ageing; Distributional effects; Inequality; Social mobility; Taxes on wealth and spending; Wealth